Incidência do imposto sobre serviço de qualquer natureza sobre a atividade cartorária - Gomes Neto, Guilherme Vieira (2016)
The incidence of the Municipal Tax on Services at registry activity is controversial in the courts. There are many debates about this subject, including a Direct Action of Unconstitutionality, which, however has not pacified the theme. Discussions about the basis calculation of tax, which the tax regime applies to notaries as well as about the transfer possibility to the registry services users are current themes. It adds, in the discussions mentioned, internal incompatibilities in Complementary Law nº 116/03, conflicting devices and contradictory tax rules. Some point approached in our scientific study have already been pacified, nevertheless it were discussed because are relevant to matter. In our analysis we do some considerations and indicate incompatibilities with the goal to bring differents points of view about the incidence of the Municipal Tax on Services over all the public registry.